Analysis of Leading Sectors Using the Location Quotient and Shift Share Methods in Deli Serdang Regency - Ujung, Syaqinah; Vidia Wardana; M Abdan Syakura (International Journal of Advanced Research, 2025)
This article aims to analyze the leading sectors in Deli Serdang Regency using the Location Quotient (LQ) and Shift Share Analysis (SSA) methods. The research was conducted using Gross Regional Domestic Product (GRDP) data from 2019-2023. The results of the LQ analysis show that five sectors, namely the processing industry, electricity and gas procurement, construction, transportation and warehousing, as well as the provision of funds and food and drink are the leading sectors with LQ values ​​> 1. SSA analysis strengthens these findings by showing that leading sectors have strong local competitiveness, especially the transportation and warehousing sectors which have a positive Regional Shift Effect. On the other hand, some sectors such as the processing industry, although making a significant contribution to GRDP, show a decline in local competitiveness, indicating the need for policy intervention. This research provides a strong basis for local governments to allocate resources and investment more effectively to support sustainable economic growth in Deli Serdang Regency.